Phase I study of PT-112, a novel pyrophosphate-platinum immunogenic cell death inducer, in advanced solid tumours. (July 2022) - Karp, Daniel D.; Camidge, D. Ross; Infante, Jeffery R.; Ames, Tyler D.; Price, Matthew R.; Jimeno, José; Bryce, Alan H.
Summary: Background: PT-112, the first pyrophosphate-platinum conjugate, causes immunogenic cell death in experimental models, leading to recruitment of tumour-infiltrating lymphocytes. PT-112 also associates with bone (osteotropism), likely driven by its pyrophosphate moiety. This is the first-in-human study of PT-112 monotherapy, exploring its safety and efficacy in a patient population where standard of care therapies were exhausted and novel treatment options are needed. Methods: Patients with progressing, advanced solid tumours received PT-112 intravenously (1 h) on days 1, 8, 15 of a 28-day cycle in an open-label, multi-centre 3 + 3 dose-escalation trial, conducted at four US research sites. The primary objective was to assess safety and pharmacokinetics, and to identify a recommended phase 2 dose (RP2D). Eligibility criteria included: age ≥18 years, Eastern Collaborative Oncology Group (ECOG) Performance Status of 0–1, and disease evaluable by Response Evaluation Criteria in Solid Tumours (RECIST) v1·1 or by informative tumour markers. Patients receiving ≥1 dose of PT-112 were included in the safety and pharmacokinetic analyses, with the exploratory efficacy analysis including patients receiving ≥1 dose at 125 mg/m 2 . This study is registered at ClinicalTrials.gov, number NCT02266745, with the dose-escalation portion of the study closed. Findings: Between July 7th, 2014 and September 18th, 2018, 66 heavily pre-treated patients (median 4 prior lines, IQR 2–6) were enrolled and treated across 11 doses (12–420 mg/m 2 ). Treatment-related adverse events included fatigue (23 patients, 35%), nausea (16 patients, 24%), and peripheral neuropathy (14 patients, 21%). Grade 3 events were experienced by 18 patients (27%), with no grade 4–5 events observed. The recommended phase 2 dose was determined to be 360 mg/m 2 . Nine (17%) of the 54 efficacy evaluable patients achieved progression-free survival ≥6 months. Durable partial responses were induced in non-small cell lung cancer (NSCLC), small cell lung cancer (SCLC), and thymoma. Radiographic and serum marker reductions were observed among ten patients with metastatic castration resistant prostate cancer, four of whom survived two years or longer. Interpretation: PT-112 is safe and well-tolerated in a heavily pre-treated population. Prolonged responses were noted against thymoma and lung cancer, along with radiographic and serum marker improvement in prostate cancer. Given the heterogeneous patient population, subsequent studies will be needed to characterize the risk/benefit ratio in more homogenous settings. Further development of PT-112 is ongoing, as single-agent and in combination with immune checkpoint inhibition. Funding: Funding was provided by Promontory Therapeutics Inc.